Effect of A Sun Protection Intervention on the Immune Response to Measles Booster Vaccination in Infants in Rural South Africa1. (3rd October 2018) - Wright, Caradee Y.; Lucas, Robyn M.; D'Este, Catherine; Kapwata, Thandi; Kunene, Zamantimande; Swaminathan, Ashwin; Mathee, Angela; Albers, Patricia N.
Abstract: The incidence of many serious childhood infections can be reduced by vaccination. High sun exposure at the time of vaccination has been associated with a reduced antigen‐specific immune response. We hypothesized that providing sun protection advice and equipment to mothers of children who were waiting to be vaccinated would result in a more robust immunization response. We conducted a pilot study in 2015/2016 (data analyzed in 2017–2018) among 98 Black African children ( 18 months of age) receiving the booster measles vaccination at two clinics in South Africa. Clinics were randomized to receive (or not) sun protection advice and equipment. We recorded demographic information on children and mothers and data on the child's usual sun exposure. At approximately 4 weeks' postmeasles vaccination, we measured measles immunoglobulin G levels in children. All children with blood results ( n = 87, 89%) across both groups had antibody titers higher than 200 mIU mL −1 which was considered the protective antibody concentration. There was no statistically significant difference in titers between groups: geometric difference in mean titers 1.13 mIU mL −1 (95% CI 0.85, 1.51; P = 0.39) and 1.38 mIU mL −1 (95% CI 0.90, 2.11, P = 0.14) for unadjusted and adjusted analyses, respectively. This study demonstrated that a sun protection intervention study could be performed in a developing‐world pediatric vaccination setting. Although the sun protection intervention around the time of vaccination was not associated with a higher antibody level, given the potential importance of such an effect, a larger study should be considered. Abstract : High sun exposure at the time of vaccination has been associated with a reduced antigen‐specific immune response. We hypothesized that providing sun protection advice and equipment to mothers of children waiting to be vaccinated would result in a more robust immunization response. This was a pilot study among 98 Black African children receiving the booster measles vaccination at two clinics in South Africa. Clinics were randomized to receive (or not) sun protection advice and equipment. Although the intervention was not associated with a higher antibody level, given the potential importance of such an effect, a larger study should be considered.